Estudio y aplicación de métodos analíticos para la extracción de parámetros eléctricos del modelo de un solo diodo para distintas tecnologías de módulos fotovoltaicos - Perich Ibáñez, Renzo Alberto (2020)
The single-diode model is used to characterize a photovoltaic (PV) solar cell using an equivalent circuit and an equation that depends on five electric parameters. Three analytical methods are applied to extract the five parameters from an Aluminium Back Surface Field (Al-BSF) PV module using 500 experimental current-voltage (I-V) curves measured in the 100-1000W/m2 range. Two of these methods are also applied to four thin-film PV modules, using four experimental I-V curves measured at an irradiance of 1000 W/m2 and air temperature 25℃. While parameter extraction methods have been studied before, this work offers a new perspective by applying the techniques to outdoor PV modules in Lima-Peru and, on the other hand, thin-film technologies located in Jaen-Spain. Results are presented by comparing the measured I-V curve with the ones modelled using the extracted parameters. The Normalized Root Mean Square Error (NRMSE) is calculated to evaluate and compare each extraction method. Values of NRMSE are then grouped by irradiance using a series of boxplots or bar charts to better visualize the success of each extraction method. The results indicate that the method proposed by Phang et al. is very robust, obtaining low values for error across the different irradiances and technologies (median NRMSE of 0.20 % for silicon and 0.50-1.10 % for thin-films). The Blas et al. method obtained low error with the silicon module (median NRMSE of 0.21 %), it was not applied to thin-films in this study. Finally, the Khan et al. method showed greater error than the other two when applied to the Al-BSF and thin-film modules, with noticeably higher error when applied to amorphous silicon modules (median NRMSE of 0.30 % for silicon and 1.77-6.73 % for thin-films).